Analysis of Flood Vulnerability using Geographic Information Systems in the Kahayan Watershed, Gunung Mas District, Central Kalimantan: Analisis Tingkat Kerawanan Banjir Menggunakan Sistem Informasi Geografis Pada DAS Kahayan Kabupaten Gunung Mas, Kalimantan Tengah - Hendrik Segah; Alfredo Liano; Santosa Yulianto; Setiarno Setiarno; Yanciluk Yanciluk (Journal of Peat Science and Innovation, 2022)
This study aims to determined the level of flood vulnerability and most dominant factors that cause flood vulnerability in the Kahayan watershed, Gunung Mas District in Central Kalimantan. This study used a quantitative method by looking at the effect of each flood parameter to determine the level of flood vulnerability or vulnerable areas in the Kahayan watershed. The results are based on research carried out in the Kahayan watershed which has 4 levels of flood vulnerability classification: low vulnerability, medium vulnerability, high vulnerability, and very high vulnerability. The high level of flood vulnerability was the largest area with an area of ​​568.146 ha or 65,25% of the Kahayan watershed area of ​​Gunung Mas District as a whole, the medium vulnerability level was 185.634 ha (21,32%), very high vulnerability level was 61,716 ha (7,09 %), and low vulnerability was the area with the smallest area of ​​55.231 ha (6,34%) of the total area of ​​the Kahayan watershed in this district. The sub-districts with the highest area at a very high level of flood susceptibility were Tewah sub-district and Kurun sub-district. The most dominant factor that causes flood vulnerability in the Kahayan watershed area of Gunung Mas District was the slope that reaches 0-8% which was included in the flat category, with 3 land criteria, namely floodplain areas, river border areas, and basin areas.